Exploring the Links between Renewable Energy, FDI, Environmental Degradation, and International Trade in Selected Developing Countries - Nasim, Ismat; Boukhris, Mohamed; Kayani, Umar Nawaz; Bashir, Farrukh; Arslan Haider, Syed (International Journal of Energy Economics and Policy, 2023)
Trade may be significantly impacted by Foreign Direct Investment (FDI), which refers to investments made outside of the investor's place of origin. Carbon emissions, in particular those that are the result of industrial activity and transportation, have the potential to have a number of important effects on commerce on both the national and international levels. The environmental, economic, and social repercussions of these effects are intricately interwoven with one another. Because it has an immediate bearing on a nation's production capacity, level of competitiveness, and the kinds of products and services that may be exported from or imported into the nation, the value added in industry has a considerable influence on international commerce. The level of government spending may have a considerable impact on the way a nation does in terms of commerce. There are several facets of commerce that might be affected, either favorably or badly, by the method that a government utilizes to distribute its money. The current study aims to examine the linkages among renewable energy, FDI, Environmental degradation and their impact on trade. The findings of study are obtained from a panel of 58 developing countries from 2000 to 2022. The results of Panel unit roots and Kao co-integration tests recommend to apply the panel ARDL to get the empirics of desirable relationships. The results of the study recommend that it is essential for governments to find a balance when making choices about their expenditures in order to guarantee that the resources allotted support sustainable economic growth, improve trade competitiveness, and fit with larger development goals. Spending decisions made by the government that are both strategic and well-targeted have the potential to play a significant part in improving the economic performance of a nation and its integration into the global economy.